Sacred Groves as Living Heritage: A Socio-Cultural Analysis of Biodiversity Conservation in Tamil Nadu (International Journal of Food and Nutritional Sciences, 2023)
Today, numerous global afforestation projects are underway. The United Nations has allocated substantial funds through various conferences to expand forested areas. Deforestation remains a significant contributor to global warming, rising sea levels, and other climate-related issues. Consequently, afforestation is deemed crucial in the current context. To achieve this, various programs and policies are being put into action. Afforestation is also the 15th target of the Sustainable Development Goals (SDGs), and all nations are striving to implement this initiative in diverse ways. This afforestation project has been successfully implemented by the Tamil society through its cultural activities for a long time in the name of ‘Kovilkaadu’ known as Sacred Groves, Temple Forest centered on Deity. In India, from ancient times, there has been a tradition of worshiping deities Due to faith in these deities, people everywhere have come to revere and worship rocks, trees, weapons like swords and bows, and even animals. These practices have mostly originated from forested regions. The animals and birds that inhabit the sacred groves, regardless of their origin or reason, have come here without being harmed, and the wild animals play without being disturbed. The elders of each village have passed down stories, myths about the unique way each temple forest is formed, instilling fear and faith among the people, ensuring their protection even today. Therefore these groves are referred to as temple forests. If these forests are converted for any other purpose, the indigenous people who protect them will believe that the deities themselves will punish them, not just through legal action or penalties, but also by destroying the deities. Thoughts on the growth of forests in Tamil sangam ancient literature have been recorded. This article discusses the importance of forests in the current Sustainable Development Goals, the structure of temple forests in the Tamil cultural tradition, how they are conserved, and the biodiversity of Kovilkadu in tamilnadu